AMR-Intervene: a social–ecological framework to capture the diversity of actions to tackle antimicrobial resistance from a One Health perspective. (14th October 2020) - Léger, Anaïs; Lambraki, Irene; Graells, Tiscar; Cousins, Melanie; Henriksson, Patrik J G; Harbarth, Stephan; Carson, Carolee; Majowicz, Shannon; Troell, Max; Parmley, E Jane; Jørgensen, Peter S; Wernli, Didier
Abstract: The global threat of antimicrobial resistance (AMR) requires coordinated actions by and across different sectors. Increasing attention at the global and national levels has led to different strategies to tackle the challenge. The diversity of possible actions to address AMR is currently not well understood from a One Health perspective. AMR-Intervene, an interdisciplinary social–ecological framework, describes interventions to tackle AMR in terms of six components: (i) core information about the publication; (ii) social system; (iii) bio-ecological system; (iv) triggers and goals; (v) implementation and governance; and (vi) assessment. AMR-Intervene provides a broadly applicable framework, which can inform the design, implementation, assessment and reporting of interventions to tackle AMR and, in turn, enable faster uptake of successful interventions to build societal resilience to AMR.